2008
DOI: 10.1016/j.tice.2007.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Shell repair process in the green ormer Haliotis tuberculata: A histological and microstructural study

Abstract: In the present paper, juvenile and adult shells of the green ormer Haliotis tuberculata ('Oreille de Saint-Pierre') were perforated in a zone close to the shell edge and the shell repair process was followed at two levels: (1) by observing the histology of the calcifying mantle in the repair zone and (2) by analyzing with SEM the microstructure of the shell repair zone. Histological data clearly show the presence of calcium carbonate granules into the connective tissues, but not in the epithelial cells. This s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 37 publications
2
50
0
Order By: Relevance
“…it sometimes withdraws from around the repair zone. A similar phenomenon has been recently observed in the abalone Haliotis tuberculata (Fleury et al 2008). A complex functioning of the mantle can also be inferred from the analyses of the organic matrix.…”
Section: Discussionsupporting
confidence: 80%
“…it sometimes withdraws from around the repair zone. A similar phenomenon has been recently observed in the abalone Haliotis tuberculata (Fleury et al 2008). A complex functioning of the mantle can also be inferred from the analyses of the organic matrix.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that calcium, in some form, is also stored in the mantle. Similar granules have been described in other species of molluscs (Marin et al 2012) and have been suggested to provide a source of calcium for shell repair (Fleury et al 2008). Also during the veliger stage, minimal staining in the shell suggests that the shell deposition may not occur continuously.…”
Section: Discussionsupporting
confidence: 71%
“…Laboratory studies of biological responses to damage (e.g. Sleight et al, 2015;Fleury et al, 2008) have involved drilling small holes in shells: under these in vitro conditions the holes become occluded within 2-4 months by formation of new material on the inside, but the holes themselves remain visible. Others have presented evidence to suggest that shells in the wild are normally repaired within 3 months (Shanks and Wright, 1986).…”
Section: Introductionmentioning
confidence: 99%